PyGlobal: A toolkit for automated compilation of DFT-based descriptors - Nath, Shilpa R.; Kurup, Sudheer S.; Joshi, Kaustubh A. (Journal of computational chemistry, 2016)
Density Functional Theory (DFT)‐based Global reactivity descriptor calculations have emerged as powerful tools for studying the reactivity, selectivity, and stability of chemical and biological systems. A Python‐based module, PyGlobal has been developed for systematically parsing a typical Gaussian outfile and extracting the relevant energies of the HOMO and LUMO. Corresponding global reactivity descriptors are further calculated and the data is saved into a spreadsheet compatible with applications like Microsoft Excel and LibreOffice. The efficiency of the module has been accounted by measuring the time interval for randomly selected Gaussian outfiles for 1000 molecules. © 2016 Wiley Periodicals, Inc. A Python‐based toolkit designed for the purpose of automating the calculation of Global reactivity descriptors such as electronegativity, global hardness, global softness, and chemical potential from the energy values of the highest occupied and lowest occupied molecular orbitals of a molecular system.